Design and experimental verification of a new multi-functional bridge seismic isolation bearing - Xing, Chen-xi; Wang, Hao; Li, Ai-qun; Wu, Ji-rong (Journal of Zhejiang University. A. Science, 2012)
A new multi-functional bridge seismic isolation bearing （MFBSIB） is designed and its mechanical model is developed in this paper. Combining an upper sliding device and a lower energy dispassion isolation device effectively, the new MFBSIB can adjust the deformation caused by temperature, vehicle breaks, and concrete creep, etc., in addition to dissipating energy. The switch of ＇slide-isolation＇ is achieved and the efficiency of both upper and lower parts is validated through experiment with a model. The shear performance curve established in this paper is verified to be efficient in describing the mechanical characteristics of the bearing through experiment. It is proved through both numerical calculation and experimental analysis that the new MFBSIB is endowed with enough vertical rigidity, good energy dissipation ability, stable overall performance, and good realiza- tion in expected goals. Its performance is slightly influenced by shear stress, while affected by vertical pressure, loading frequency, slide limit, etc., diversely. The results could provide reference for study and application of the new MFBSIB.